Global inequality and the Trump administration. Issue 3 (2nd January 2019) - Mayer, Frederick W.; Phillips, Nicola
Abstract: Since US President Donald J. Trump took office in January 2017, the future of the global economy has looked distinctly uncertain. This is not because a process of clear and purposeful change can be said to be underway. Instead, it is because of a pattern of piecemeal, inconsistent and contradictory fragments of policy, both domestic and international in orientation, in the arenas of trade, taxation, business relations, finance and banking, social and welfare provision, immigration, and environmental protection, whose cumulative significance remains unclear. The modest task of this essay is therefore to sketch the contours, patterns, inconsistencies and confusions presented by the Trump administration's approach to shaping the US economy and, by extension, the global economic order, and on that basis to offer an interpretation of its emerging implications for inequality both within the United States and across the world.